2018
DOI: 10.3389/fphar.2018.00093
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Effects of a Kappa Opioid Receptor Antagonist in the Forced Swim Test

Abstract: There is growing evidence that kappa opioid receptor (KOR) antagonists could be a useful class of therapeutics for treating depression and anxiety. However, the overwhelming majority of preclinical investigations examining the behavioral effects of KOR antagonists have been in male rodents. Here, we examined the effects of the long-acting KOR antagonist nor-binaltophimine (norBNI) on immobility in the forced swim test in males and females of two different rodent species (C57Bl/6J and California mice). Consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 58 publications
4
23
0
Order By: Relevance
“…Female mice and rats have been reported to be less sensitive than males in their responses to kappa opioid agonists and antagonists (Russell et al, 2014; Abraham et al, 2018; Laman-Maharg et al, 2018; Williams and Trainor, 2018). These sex differences raise important questions about the utility of kappa antagonists in the treatment of stress-disorders in women.…”
Section: Resultsmentioning
confidence: 99%
“…Female mice and rats have been reported to be less sensitive than males in their responses to kappa opioid agonists and antagonists (Russell et al, 2014; Abraham et al, 2018; Laman-Maharg et al, 2018; Williams and Trainor, 2018). These sex differences raise important questions about the utility of kappa antagonists in the treatment of stress-disorders in women.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that intracerebroventricular (ICV) infusion of either norBNI (Mague et al 2003;Pliakas et al 2001) or 5'-GNTI (Mague et al 2003) decreased immobility in the FST in a dose-dependent manner in rats. Additionally, systemic norBNI reduces immobility in the FST in mice (Falcon et al 2016;Laman-Maharg et al 2018;McLaughlin et al 2003) and rats (Reed et al 2012). Similarly, JDTic reduced immobility at higher dosages tested in the FST in rats; however, in this specific experiment, both norBNI and desipramine had no effect (Beardsley et al 2005).…”
Section: Kor Antagonists Show Efficacy In the Fst Anti-depressant Screening Testmentioning
confidence: 69%
“…Female rats have been shown to be less sensitive than male rats to the depressive-like effects of KOR agonists (Russell et al 2014) and female guinea pigs are less sensitive than male guinea pigs to the effects on pain (Wang et al 2011). One experiment found that the antidepressant effects of norBNI on the FST in two different strains of male mice were not found in females (Laman-Maharg et al 2018). Interestingly, one PET imaging study of naltrexone in humans reported a higher KOR availability in men than in women (Vijay et al 2016).…”
Section: Sex Differencesmentioning
confidence: 99%
“…In a place aversion assay, females form place aversions to a lower dose of the KOR agonist U50,488 than males [38, 39]. However, in a forced swim test norBNI reduced immobility in males but not females [40], consistent with other studies suggesting that males may be more sensitive KOR than females [41, 42]. Previous work showed that activation of KOR within the DRN induced anxiety- and depression-like behavior, so we expected that similar responses in stress naïve mice.…”
Section: Introductionmentioning
confidence: 99%